1992
DOI: 10.1002/bit.260400802
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and stoichiometry of growth of plant cell cultures of Catharanthus roseus and Nicotiana tabacum in batch and continuous fermentors

Abstract: Plant cell suspension cultures of Catharanthus roseus and Nicotiana tabacum were grown in stirred tank bioreactors operated in batch and continuous mode. The stoichiometry of growth of both species in steady-state glucose limited chemostats was studied at a range of different dilution rates. A linear relation was applied to describe specific glucose uptake, oxygen consumption, and carbon dioxide production as a function of the growth rate. Specific respiration deviated greatly from the linear relation. An unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…While literature data for the product formation model parameters are not readily available, the growth model parameters reported here are in good agreement with the literature data. The values for m max (0.323/day) and Y X|S (0.474 g/g) found in this study are very similar to the values reported by Van Gulik et al (1992) for Nicotiana tabacum cell suspension culture (m max ¼ 0.3264/day and Y X|S ¼ 0.57 g/g). The validity of the dynamic state model was further scrutinized using data from another three independently conducted reactor runs (runs #2$4; each has a different initial glucose concentration and slightly different initial cell density) using the model parameter values shown in Table I.…”
Section: Development Of a Dynamic Process Modelsupporting
confidence: 89%
“…While literature data for the product formation model parameters are not readily available, the growth model parameters reported here are in good agreement with the literature data. The values for m max (0.323/day) and Y X|S (0.474 g/g) found in this study are very similar to the values reported by Van Gulik et al (1992) for Nicotiana tabacum cell suspension culture (m max ¼ 0.3264/day and Y X|S ¼ 0.57 g/g). The validity of the dynamic state model was further scrutinized using data from another three independently conducted reactor runs (runs #2$4; each has a different initial glucose concentration and slightly different initial cell density) using the model parameter values shown in Table I.…”
Section: Development Of a Dynamic Process Modelsupporting
confidence: 89%
“…Up to this point we have assumed that sugar is converted only to biomass and CO 2 . Plant cell cultures are, however, capable of producing extracellular polysaccharides (van Gulik et al, 1992). Furthermore, extracellular proteins and the products of cell lysis also accumulate in the medium, and these are considered byproducts in hairy root cultures (Kwok and Doran, 1995).…”
Section: Carbon Balancementioning
confidence: 99%
“…Microalgal cells can trap light as the energy source and assimilate CO 2 as the carbon source. It is important to note that the organic substrates can also be utilized as the carbon and energy sources by some microalgae [38,39,40]. Changes in the proportions of individual photosynthetic pigments may occur in response to variation in the intensity of light and a species in which a particular type of pigmentation is determined genetically may become adapted to an environment [40].…”
Section: Discussionmentioning
confidence: 99%